THE PROBATIONARY PERIOD FOR A FIXED-TERM EMPLOYMENT CONTRACT - T. Suvalova (Вестник университета)
In the article the peculiarities of concluding a fixed term employment contract when hiring employees whose job is temporary, seasonal. Therefore, the analysis of the duration of the probationary period, noted some categories of people having the right not to be tested. Concludes that further cooperation with the employee: upon successful completion of the employee continues to work a specified period, in case of unsuccessful passing - the principal has the right to terminate the contract at any time.